If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 7) = -2x + -44 Reorder the terms: -5(7 + x) = -2x + -44 (7 * -5 + x * -5) = -2x + -44 (-35 + -5x) = -2x + -44 Reorder the terms: -35 + -5x = -44 + -2x Solving -35 + -5x = -44 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -35 + -5x + 2x = -44 + -2x + 2x Combine like terms: -5x + 2x = -3x -35 + -3x = -44 + -2x + 2x Combine like terms: -2x + 2x = 0 -35 + -3x = -44 + 0 -35 + -3x = -44 Add '35' to each side of the equation. -35 + 35 + -3x = -44 + 35 Combine like terms: -35 + 35 = 0 0 + -3x = -44 + 35 -3x = -44 + 35 Combine like terms: -44 + 35 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 2(x-8)+3x=-1 | | 2/3x-3/2=-1/5 | | g=77-22 | | 3x-7=6x-4 | | 4x+8=16-2x | | 2a^2-3=-5a | | x+36=2x+8 | | 4b+8=16-2x | | 13x-1=4(3x+3)-11 | | 2(3x+7)=-44+4 | | 7k^2=5-34k | | m-3+13=20 | | 2x-3=2x+2 | | 5n^2-40n=0 | | g+48=54 | | 6y+6=2y+8 | | 9-4x=2x-3 | | 45/4m=35/3 | | f=53-24 | | 5k^2+20k=-15 | | ln(x)+ln(2x)=0 | | 52y-3.1=12 | | 19(v+4)-3v=4(4v+4)-24 | | 5x6/15-2 | | 2-x=2x-6 | | 3m^2-6m=9 | | 4.5(x+5.5)=4.5(x+5.5) | | 13t+10=-3 | | 5t+6=26 | | x^3=6x+x^2 | | 26+3y-3=15y-12-5y | | 5a-10=-5a |